Composite neonatal morbidity indicators using hospital discharge data: A systematic review. Issue 3 (23rd March 2020) - Lebreton, Elodie; Crenn‐Hébert, Catherine; Menguy, Claudie; Howell, Elizabeth A.; Gould, Jeffrey B.; Dechartres, Agnès; Zeitlin, Jennifer
Abstract: Background: Neonatal morbidity is associated with lifelong impairments, but the absence of a consensual definition and the need for large data sets limit research. Objectives: To inform initiatives to define standard outcomes for research, we reviewed composite neonatal morbidity indicators derived from routine hospital discharge data. Data sources: PubMed (updated on October 12, 2018). The search algorithm was based on three components: "morbidity, " "neonatal, " and "hospital discharge data." Study selection and data extraction: Studies investigating neonatal morbidity using a composite indicator based on hospital discharge data were included. Indicators defined for specific conditions (eg congenital anomalies, maternal addictions) were excluded. The target population, objectives, component morbidities, diagnosis and procedure codes, validation methods, and prevalence of morbidity were extracted. Synthesis: For each study, we assessed construct validity by describing the methods used to select the indicator components and evaluated whether the authors assessed internal and external validity. We also calculated confidence intervals for the prevalence of the morbidity composite. Results: Seventeen studies fulfilled inclusion criteria. Indicators targeted all (n = 4), low‐/moderate‐risk (n = 9), and very preterm (VPT, n = 4) infants. Components were similar for VPT infants, but domains and diagnosis codes within domains varied widely for all and low‐/moderate‐risk infants. Component selection was described for 8/17 indicators and some form of validation reported for 12/17. Neonatal morbidity prevalence ranged from 4.6% to 9.0% of all infants, 0.4% to 8.0% of low‐/moderate‐risk infants, and 17.8% to 61.0% of VPT infants. Conclusions: Multiple neonatal morbidity indicators based on hospital discharge data have been used for research, but their heterogeneity limits comparisons between studies. Standard neonatal outcome measures are needed for benchmarking and synthesis of research results.